Negative Tone and Readability in Management Discussion and Analysis Reports: Impact on The Cost of Debt - Eka Sari Ayuningtyas; Iman Harymawan (Universitas Airlangga, 2021)
Companies use disclosure as a strategy to transfer and communicate selected information to stakeholders. This study examines the association between the firm's textual disclosure strategy and cost of debt by looking at the tone and readability of Management Discussion and Analysis (MDandA) reports and using a sample of 1596 Indonesian listed companies from all industries except the financial industry, from 2011 to 2018, and using ordinary least square (OLS) regression to test the research hypotheses. The findings suggest that both negative tone and poor readability level are associated positively with the cost of debt. This paper contributes to knowledge of the important aspects firms need to consider when setting their disclosure strategies, mainly how the tone and readability of firms' annual reports may be interpreted by users/creditors and affect the amount they will charge the firm for debt.